A study of Summer Rainfall on the Southern Coast of the Caspian Sea Using WRF and Satellite Numerical Forecasting Models - Donya Sadegh Nezhad; Ebrahim Fatehi; Gholam Ali Kamali; Zahra Ghassabi (Nīvār)
The amount of precipitation plays an essential role in the occurrence of floods. The more accurate the rainfall forecast is, the better the flood can be predicted. Numerical weather forecasting models such as WRF usually do not have suitable outputs for predicting the amount of precipitation in the first hours of implementation; This is intensified in the summer season on the southern shores of the Caspian Sea in the provinces of Gilan and Mazandaran. Because most of the heavy rains in this season occur in the form of convection and in small spatial and temporal dimensions. Using the extrapolation of GPM, TRMM satellite products to predict short-term rainfall up to 24 hours can be a suitable method to achieve the amount of rainfall with more appropriate resolution and accuracy. In this research, the occurrence of two daily precipitation systems of more than 40 mm in summer on the southern shores of the Caspian Sea was investigated. The results showed that the use of GPM, TRMM satellite products for short-term rainfall forecast up to 24 hours is more accurate compared to the model output. Statistical analysis showed a good correlation between model prediction and ground data and satellite data